LANGUAGE TEACHING AND MOTIVATION: A PSYCHOLOGICAL PERSPECTIVE - Saidaposhsho Azizova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: motivation plays a pivotal role in language teaching and learning. It drives learners to persist in the often challenging process of acquiring a second or foreign language and deeply influences their success. Drawing from psychological theories such as intrinsic and extrinsic motivation, self-determination theory, and the socio-educational model, this article explores the interplay between motivation and effective language teaching. We examine strategies teachers can employ to foster motivation, including creating engaging learning environments, incorporating culturally relevant materials, and employing goal-setting techniques. The article also discusses barriers to motivation, such as anxiety and lack of self-efficacy, and offers evidence-based approaches to mitigate these challenges. By integrating psychological insights with practical teaching methods, this work aims to provide educators with a comprehensive understanding of how motivation shapes language learning outcomes.